(untitled) (LEARNing Landscapes, 2013)
Building on Hillocks’ (1995) concepts of the declarative and procedural knowledge that writers need in order to craft effective writing, this article explores the writing process of one pre-service teacher as she moved from a personal narrative to an essay to a digital story. The authors argue that digital writers—in addition to needing declarative and procedural knowledge—must also understand knowledge of technology in order to more fully realize the potential of digital storytelling. Implications for teachers and teacher educators are discussed in relation to Mishra and Koehler’s (2008) "technological pedagogical content knowledge,” or TPACK.